1984
DOI: 10.1093/jn/114.7.1260
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Parenteral Magnesium Load Test in Weanling Rats

Abstract: The parenteral magnesium (Mg) load test has reliably identified rats fed two extremes of dietary Mg, but tests of intermediate levels have not been found. The present study was designed to learn: 1) whether the parenteral Mg load test reflects a series of different dietary levels of Mg, rather than just the extremes; 2) what relationship exists between Mg retention and Mg in plasma and in bone at the different dietary levels of Mg; and 3) how the different dietary levels of Mg affect weight gain. Weanling rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Interestingly, addition of Mg2, to platelets gelfiltered in the absence of Mg2' and Ca2+ promotes optimal aggregation and secretion responses while Ca2+ promotes disaggregation (50,51 ). It is possible that an initial burst of Mg2+ provided by damaged cells, which contain intracellular Mg2+ concentrations in excess of 15 mM (25)(26)(27)(28), and exposure to type I collagen could collectively induce the aggregation response. Macrophages and neutrophils also become activated during this phase, extravasating through the blood vessel wall, surrounding tissue and into the wound site.…”
Section: 33 34)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, addition of Mg2, to platelets gelfiltered in the absence of Mg2' and Ca2+ promotes optimal aggregation and secretion responses while Ca2+ promotes disaggregation (50,51 ). It is possible that an initial burst of Mg2+ provided by damaged cells, which contain intracellular Mg2+ concentrations in excess of 15 mM (25)(26)(27)(28), and exposure to type I collagen could collectively induce the aggregation response. Macrophages and neutrophils also become activated during this phase, extravasating through the blood vessel wall, surrounding tissue and into the wound site.…”
Section: 33 34)mentioning
confidence: 99%
“…Under normal physiologic conditions the concentration of intracellular Mg2+ in the typical mammalian cell is reported to be between 15 and 30 mM and that of Ca2+ is only -1-2 mM (25)(26)(27)(28). On the other hand, extracellular levels of these two cations are about 1.0 and 2.5 mM, respectively (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…The test is based on Urinary excretion of an intravenous 26 Mg dose MK Wälti et al normal kidney regulation of body stores of Mg, excreting an excess in the normal subject and retaining the mineral in deficiency (Caddell et al, 1984). Moreover, rat studies have demonstrated that tissues from Mg-deficient rats had a higher Mg uptake after intraperitoneal injection of 28 Mg than controls (Caddell et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…121 The CMS creates relatively strong obligations, but is tempered by words and phrases such as 'whenever possible and appropriate', 'promote', 'endeavour', 'to the extent feasible and appropriate' which are open to interpretation. 122 Moreover, enabling minimisation as an alternative to avoidance, regarding activities that seriously impact migration, reduces the strength of any obligation. The restrictions listed in Article III apply to Appendix I species and do not benefit the case study species in this research.…”
Section: The Cms Approachmentioning
confidence: 99%